Influence of thermophysical properties of the solid dependence from temperature on the thermal characteristics and erosion under the action of high-power pulsed ion beams; Методология проектирования молодежного научно-инновационного пространства как основа подготовки современного инженера - Truntseva R. P. (Integrity of traditions and innovations as the basis for the development of modern engineering science, 2014)
Заглавие с экрана